Ophthalmology pearls - Gault, Janice A. (Hanley & Belfus, 2003)
Wills Eye Hospital, Philadelphia, PA. Exam review presents patient scenarios with exam and lab findings, color images, and the opportunity for the reader to make a diagnosis and form a treatment plan. The 'whole story' is revealed on the second page of the two-page format. Tips and pearls are included. Softcover.